Converging with World Trends: The Emergence of the Cosmopolitan Citizen in Post-Socialist Romanian Citizenship Education - Szakács, Simona (JSSE - Journal of Social Science Education, 2013)
Based on thematic content analysis of textbooks, curricula, and an overview of educational legislation after the 1989 change of political regime in Romania, this paper presents empirical evidence to argue that that postsocialist citizenship education displays surprising similarities with converging post-war changes in the concept of the ‘good citizen’. The findings suggest a complex picture of change combining liberal, communitarian and cosmopolitan renditions of the new citizen, all having a common thread: the shift towards a post-national ethos delinking the citizen from the exclusive purchase of national belonging and decoupling citizen action from the absolute duty to the patria. Such significant changes are often overlooked due to the dominant focus on the failures to comply with an idealized Western liberal model. However, they invite us to reconsider current understandings of both the pitfalls and the opportunities of post-socialist citizenship education by considering them from a different angle: that of wider socio-cultural change that is gradually being institutionalised at the world level.